1998
DOI: 10.1007/bf02787709
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic DNA-and RNA-hydrolyzing antibodies from milk of healthy human mothers

Abstract: Various catalytically active antibodies (Abs), or abzymes, have been detected recently in the sera of patients with autoimmune pathologies, in whom their presence is probably associated with autoimmunization. Normal humans are generally not considered to have abzymes, since no obvious immunizing factors are present. Here is shown by different methods that IgG from the milk of normal females possesses both DNase and RNase activities. The activities were also present in the IgG F(ab')2 and Fab fragments. Affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 58 publications
(114 citation statements)
references
References 21 publications
1
113
0
Order By: Relevance
“…Some cytotoxic Abs to microorganisms or mammalian cells trigger target cell death by DNA or protein hydrolysis (53)(54)(55)(56)(57)(58)(59) or by production of toxic oxidative molecules (i.e., H 2 O 2 , O 3 , and hydroxide radials) via catalyzing water oxidation reactions (13)(14)(15). Our data exclude the possibility that the anti-O6ad Abs exert their bactericidal action through DNase (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Some cytotoxic Abs to microorganisms or mammalian cells trigger target cell death by DNA or protein hydrolysis (53)(54)(55)(56)(57)(58)(59) or by production of toxic oxidative molecules (i.e., H 2 O 2 , O 3 , and hydroxide radials) via catalyzing water oxidation reactions (13)(14)(15). Our data exclude the possibility that the anti-O6ad Abs exert their bactericidal action through DNase (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Chromatography of IgGs under "acid shock" conditions was carried out using FPLC gel-filtration on Superdex 200 HR 10/30 (Pharmacia) using 0.1 M glycine-HCl, pH 2.6, as described previously [26][27][28][29][30][31][32][33]. Fractions collected after the gel-filtration were dialyzed against 20 mM Tris-HCl, pH 8.0, and used in activity assays as described below.…”
Section: Antibody Purificationmentioning
confidence: 99%
“…Pregnancy could "activate" or "trigger" autoimmune-like manifestations in clinically healthy women, and a sharp exacerbation of autoimmune reactions can occur in some cases soon after childbirth [6][7]. Natural Abzs were also described in the milk of healthy human mothers including sIgAs and/or IgGs possessing DNase and RNase [26][27][28] or ATPase activities [29][30], and protein kinase activity [31][32] which are the first natural Abzs with synthetic activity. These Abzs show specific activities significantly higher than Abs found in the sera of AI patients.…”
Section: Introductionmentioning
confidence: 99%
“…Natural Abzs also occur in the milk of healthy human mothers and include sIgA and/or IgG possessing DNase and RNase [25][26][27], amylolitic [28] or ATPase activities [29], and protein kinase [30] and lipid kinase activities [31] which are the first examples of natural Abzs with a synthetic activity. Human IgGs from different AD patients in cleavage of supercoiled (sc) and nicked (n) pBR322 DNA: lanes 1-10 correspond to Abs from the sera of 10 different patients; lane C 1 -DNA incubated alone; lanes C 2 and C 3 -DNA incubated with Ab from the sera of two healthy donors.…”
Section: Natural Catalytic Antibodiesmentioning
confidence: 99%
“…We have suggested that DNA-ase and RNA-ase activity Abs from human milk are not only capable of neutralizing viral and bacterial nucleic acids by complexation with them, but also can hydrolyze them; existence of DNA-ase activity in Abs raises the possibility that these Abzs may protect newborns by hydrolysis nucleic acids of infectious agents [26,27].…”
Section: Biological Role Of Abzymesmentioning
confidence: 99%